A rapid and high-throughput approach to quantify non-esterified oxylipins for epidemiological studies using online SPE-LC-MS/MS - Wang, Teng; Li, Haonan; Han, Yiqun; Wang, Yanwen; Gong, Jicheng; Gao, Ke; Li, Weiju; Zhang, Hongyin; Wang, Junxia; Qiu, Xinghua; Zhu, Tong (Analytical and bioanalytical chemistry, 2020)
Oxylipins are highly bioactive lipid mediators derived from polyunsaturated fatty acids (PUFAs) and have fundamental roles in a diverse set of homeostatic and inflammatory processes. Current targeted methods of analyzing oxylipins require long runtimes and laborious sample preparation, limiting their application to epidemiological studies. Here, we report the development of an online solid-phase extraction-liquid chromatography-triple quadrupole mass spectrometry (online SPE-LC-MS/MS) method to quantify 49 non-esterified oxylipins and PUFAs, including prostanoids, leukotrienes, lipoxins, resolvins, hydroxy PUFAs, epoxy PUFAs, and their PUFA precursors, in 50-μL samples of human serum. The new method was validated in terms of linearity, lower limits of quantification, recovery, precision, and matrix effects. The limits of quantification were in the range of 0.18 to 9 pg for oxylipins. A single 11.5-min analysis enabled the accurate (80–120% recovery), precise, and reproducible (RSD < 15%) quantification of 32 analytes at three spiked concentrations (0.1, 1, 5 ng/mL), demonstrating the suitability of this method for large-scale epidemiological studies. We successfully applied it to rapidly analyze a total of 565 serum samples from prediabetic and healthy individuals in a nested case-control panel study. Oxylipin concentrations were quantified within a range similar to those of previously published articles. Application of this approach to both healthy and prediabetic subjects found that several circulating hydroxy PUFAs, including LTB 4 , 12-HEPE, 15(S)-HETE, and 17-HDHA, were negatively associated with fasting glucose levels, indicating decreased anti-inflammatory activity and impaired glucose tolerance in diabetes progression. This new approach provides a means for high-throughput analyses of non-esterified oxylipins for epidemiological studies and will help unravel the intricate interactions of the oxylipin cascade and accelerate our understanding of the biological regulation of these important lipid mediators in human disease.